Entrenamiento de subespecialidades en otorrinolaringología (2013)
Otolaryngology is a medical and surgical specialization that is having a great development in the last years. Many fields have open in the practice of otolaryngology. Some years ago academic departments offer fellowship training opportunities, something that has become controversial. The purpose of this assay is to analize the benefits for the students, the university, otolaryngology and our country healthcare. In the same way there is an exposure of the disadvantages and seek for solutions to improve them.